Association, Principle Component and Genetic Divergnce Study in Recombinant Inbred Lines (RIL’s) Population of Rice - Sahu, Hemant; Saxena, Ritu R.; Verulkar, S. B.; Rawte, Suman (International Journal of Bio-resource and Stress Management, 2023)
Morphological characterization of seventy one rice breeding lines using 18 agronomic traits was performed. The aim of study was to determine the variability and extent of genetic diversity. Principal Component Analysis (PCA) was also performed to uncover similarities between variable and classify the genotypes. Only plant height exhibited high genetic advance and high heritability, whereas seedling height, biological yield and grain yield exhibited moderate heritability and high genetic advance. Character association of the yield attributing traits revealed significantly positive association of grain yield plant-1 with root pulling resistance, days to 50% flowering, tillers number, flag leaf width, second leaf width, spikelet fertility and biological yield. According to UPGMA cluster analysis all accessions were clustered into eleven groups. Cluster I was the biggest (including 29 lines) and cluster II, V, VIII and XI were the smallest (only one line) group. Under principal component analysis study, first six components contribute 77.54% of the variability. Component one had the contribution from the traits such as seedling height, shoot biomass, plant height, panicle length, flag leaf length, second leaf length and length of last inter-node which accounted 27.57% of the total variability. PC-2, PC-3, PC-4, PC-5 and PC-6 had 20.14%, 12.09%, 6.46%, 5.91% and 5.38% contribution to the total genotypic variability, respectively.